Differences in body composition in relation to performance level in male collegiate tennis players - Okumura, K.; Torii, S. (Medicine and Science in Tennis, 2009)
Background: It has been well known long-term sport activity has influences on body composition. Although there are many studies about tissue composition in tennis players, few studies were conducted about tissue composition according to performance level. Purpose: The purpose of this study was to investigate about tissue composition in the collegiate tennis players of different performance levels. Methods: Bone mineral content (BMC), bone mineral density (BMD) and lean mass (LM) were measured in 25 male collegiate tennis players and 10 male controls (CG) using dual-energy X-ray absorptiometry (DXA). We classified of tennis players into regular group (RG) and nonregular group (NG) according to their performance level. Side-to-side difference (SSD) was calculated as percentage of the nondominant value. Results: The main results obtained were as follows: 1.No significant differences were observed in athletic careers between RG and NG. 2.The BMD of the dominant upper limb in RG were significantly higher than those in NG and CG. 3.The SSDs of BMC, BMD and LM of upper limb in RG were significantly higher than those in NG and CG and the SSDs in NG were significantly higher than in CG. Discussion: Although athletic carriers of RG were similar to those of NG, BMD of the dominant arm and SSDs in BMC, BMD and LM in RG were significantly higher than those of NG. The players in RG swing their rackets faster and hit balls more powerful than players in NG. These athletic motions stimulate muscles and bones of the dominant arms, and those effects were probably higher in RG than in NG. Understanding specific tissue composition according to the performance level in tennis players will give important information to build training menu and prevent from injuries.